Impact of economic inequality on national stereotypes and dehumanization - Alba Álamo-Hernández; Verónica Betancor-Rodríguez; Armando Rodríguez-Pérez (Psychology, Society & Education, 2024)
Research on social perception has shown that people tend to construct a mental picture of national groups. Much research has been directed at exploring the influence of relevant contextual variables, such as economic inequality, on these representations. The purpose of this study is to investigate how economic inequality affects two key elements of social perception: the stereotypical dimensions of competence, sociability, and morality and the humanity attributed to the inhabitants of nations with high and low economic inequality. Countries with high and low objective inequality were selected and participants were asked to indicate to what extent they considered the inhabitants to be competent, sociable, and moral. We also asked to what extent they attributed humanity and capacity to experience primary and secondary emotions to the inhabitants of these countries. The study was carried out with a Spanish sample (N = 245). The results showed the existence of an ambivalent pattern in which more competence and less sociability were attributed to nations with low inequality and the opposite (less competence and more sociability) to nations with high inequality; and a significant tendency was found to attribute more morality to nations with low inequality than to those with high inequality. Parallel mediation analysis showed that only morality significantly connected economic inequality with the attribution of humanity. Significant differences were found in the attribution of humanity but not in the attribution of capacity to experience secondary emotions. The results are discussed in light of the Stereotype Content Model and system justification.